(untitled) (Global Journal of Science Frontier Research, 2014)
In this research work the level and distribution pattern of the metals: Ni, Cr, Mn, and Fe were determined in soil samples collected within Maiduguri Metropolis. Samples were collected from places of high anthropogenic activity such as automobile maintenance workshop (AMW), Car park or Bus stops (CP), and the highways (HW) to places of low activity the Residential areas (RA) at the depth of 5 to 15cm. To avoid washing away of the metals by rainfall, all collections were done during the dry season in the month of September/October 2012 to April/May of the following year 2013. These periods are period of incessant wind and sandstorm marked with low or no rainfall in this part of the country (far north-eastern part of Nigeria). Soil samples were analyzed using ICP-OES following digestion with aqua-regia and the results shows that; the levels; 14.48, 8264.17, 24.26, and 84.75μgg-1 were observed in the samples from AMW for the metals: Ni, Fe, Cr, and Mn respectively. The RA has the levels; 4.96, 804.50, 4.56, and 13.93 μgg-1 for the metals; Ni, Fe, Cr, and Mn respectively. The HW and CP had level of the metals; greater than the RA but less than the AMW. The high concentration of the metal (Fe) in the soil suggests that this metal could be mainly of natural origin with adequate contribution from anthropogenic influences. The concentrations of the metals was found to decrease with increasing distance from the places of high anthropogenic activity AMW, HW, CP to the places of less anthropogenic activities the RA. The distribution pattern of metals; Ni, Cr, Fe, and Mn in Maiduguri Metropolis could be arranged in the order; AMW > CP > HW > RA. This trend further confirms that automobiles are the main contributor of the heavy metals in the urban environment.